Enhancement of 6-gingerol extraction from bentong ginger using supercritical carbon dioxide - Kamaruddin, Muhamad Syafiq Hakimi; Chong, Gun Hean; Umanan, Fizreena; Suleiman, Norhidayah (Elsevier, 2023)
Supercritical carbon dioxide extraction is a green technology. It was used to isolate 6-gingerol from Bentong ginger (Zingiber officinale Roscoe var. Bentong). A central composite design (CCD) was employed to investigate and optimize three process conditions, namely the extraction pressure (10“30 MPa), temperature (40“60 —¦C), and particle size of the sample (300“600 µm). The method was used to model the extraction of 6-gingerol, total phenolic content, total flavonoid content, and antioxidant activity determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH). The optimum conditions were estimated to be a pressure of 25 MPa, a temperature of 40 —¦C, and a particle size of 300 µm. The highest values for 6-gingerol content (171.26 mg/g), total phenolic content (17.84 GAE mg/g), total flavonoid content (74.46 QE mg/g), and radical-scavenging activity (91.14) of dried Bentong ginger were achieved at these optimized conditions. The good fit between predicted and experimental values shows the fitness of the model employed for estimating the optimum conditions for Bentong ginger extraction. Moreover, the scCO2 system at the conditions studied was more effective than the conventional Soxhlet method for the extraction of bioactive compounds.